Renewable energy in Pakistan: Paving the way towards a fully renewables‐based energy system across the power, heat, transport and desalination sectors by 2050. Issue 1 (10th September 2021) - Sadiqa, Ayesha; Gulagi, Ashish; Bogdanov, Dmitrii; Caldera, Upeksha; Breyer, Christian
Abstract: Pakistan is currently undertaking a substantial expansion of electricity generation capacity to provide electricity for all its end‐users and to satisfy a fast‐growing economy. Adoption of low‐cost, abundant and clean renewable energy will not only fulfil its growing electricity, heat, transportation and desalinated water demand but also help achieve the goals set under the Paris Agreement. A technology‐rich energy system model applied in hourly resolution has been used for investigating the transition in 5‐year periods until 2050. This study demonstrates that a 100% renewable energy system across the power, heat, transport and desalination sectors is not only technically feasible but also economically viable. Solar photovoltaics emerges as a key technology to generate electricity and contribute a share of 92% to the total primary energy demand across all sectors by 2050. The levelised cost of energy for a 100% renewable energy system is calculated as 56.1 €/MWh in 2050, lower than 70 €/MWh for the current fossil fuel‐based system. A key feature of Pakistan's future energy system is the huge increase in demand across all energy sectors, particularly for desalinated water, which is almost 19% of the final energy demand. This share of energy for desalination is among the highest in the world. Direct and indirect electrification across all demand sectors increases the efficiency of the future energy system. Moreover, GHG emissions from all the sectors will drop to zero by 2050 in a fully sustainable energy scenario.